PENGARUH PEMBERIAN KOMBINASI KEGEL EXERCISE DAN BRIDGING EXERCISE TERHADAP PERUBAHAN FREKUENSI INKONTINENSIA URIN PADA LANJUT USIA DI YAYASAN BATARA HATI MULIA GOWA - Rijal Rijal; Hardianti Hardianti; Fadhia Adliah (Jurnal Ilmiah Kesehatan Sandi Husada, 2019)
Elderly is the stage of life process that characterized by decreasing in the body ability, so that there are many changes in anatomical and physiological, including changes in neurology, musculoskeletal, and bladder. It has an impact on weakness of pelvic muscles that cause urinary incontinence due to urethral sphincter muscle inadequate as an effort to prevent urine leakage. The treatment is performed by giving direct pelvic floor muscle support and the overall core muscle through exercises.The aim of this study is to determine the combination effect of kegel exercise and bridging excerise on changes in urinary incontinence in the elderly. This study is a pre-experimental design, with one group pretest-posttest design approach. The population is all the elderly at Batara Hati Mulia Foundation, Gowa and takes 13 people from purposive sampling technique.The Data was collected by taking primary data through interviews and based on ordinal scale frequency of urinary incontinence. This study was performed for 6 weeks by 18 exercise sessions. A paired T test is performed as statistical test and the results of pre-test and post-test analysis increased the frequency of urinary incontinence with value of p ;0,000. It shows that the combination of kegel exercise and bridging exercise has an effect on changes in frequency of urinary incontinence in the elderly.